Management Strategy and Responsibilities of Substitute Notaries for Notary Protocols - Tjandraningsih, Dewi (The International Journal of Education Management and Sociology, 2023)
The aim of this research is to analyze the management and responsibilities of a substitute Notary regarding notary protocols. And to eliminate obstacles to the management and responsibilities of substitute notaries in notary protocols. This research method uses a qualitative approach that describes the picture of what happened. Data collection techniques through interviews, observation and documentation studies. Results in the management and responsibilities of a substitute notary regarding notary protocols as a notary's professional responsibility relating to deeds, such as the notary's civil responsibility for the deeds he or she makes. Responsibility for material truth, unlawful acts, and criminal responsibility of the notary for the deed he made. Criminal acts committed by notaries in their capacity as public officials who have the authority to do deeds and the administrative responsibilities of notaries. Administrative sanctions are based on UUJN. There are administrative sanctions if a Notary violates them, namely: verbal warning, written warning, temporary dismissal, honorable dismissal, and dishonorable dismissal. Inhibiting factors in the management and responsibility of substitute notaries regarding notary protocols, namely. Lack of supervision in selecting a replacement notary, lack of strict rules and regulations, and code of ethics. Not yet on the aspects of problems and accountability of substitute notaries who violate the law. No institution supervises substitute notaries. Legal awareness is still low. There is no education for notaries.